A study on the effects of urban mining on mineral depletion - Ahyong, Andrea Maxine Y.; Enriquez, Karissa Mariel S.; Pajaron, Marjorie C. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
The purpose of this thesis is to determine whether or not urban mining significantly affects mineral depletion. Rapid industrialization and urbanization throughout the world has led to an increase in raw mining activities to obtain primary resources, and to numerous negative externalities that affect the environment and long_run growth of an economy. These are due to the fact that industrialization has increased a country_s demand for natural resources, while simultaneously increasing its production of waste. Hence, a way to mitigate these negative effects would be to pursue a circular economy approach, also known as a closed loop economy, by implementing urban mining activities and policies. By recycling waste and recovering secondary resources, a country will be able to achieve sustainable development through closing the loop of the flow of materials within an economy. This will ultimately lead to a lessened dependency on raw mining for resources, thus less negative effects on the environment, including mineral depletion. This study will examine the effects of urban mining activities on mineral depletion by regressing two groups of explanatory variables against mineral depletion. Multiple regressions will be done to explain the relationship between urban mining activities and mineral depletion, including an OLS regression method, probit regression and finally, logistic regression. The results of the sets of regressions are expected to be significant, due to the growing needs of countries to pursue sustainable development, given the condition of the world today. Further regressions will also be done, transforming and expanding the dependent variable of mineral depletion to the aggregate natural resource depletion. Currently, more and more countries are realizing this need, and are slowly transitioning from a linear economy approach to a circular economy approach. European countries were the first to transition into a circular approach, while other countries are starting to follow their lead.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Mines and mineral resources -- Environmental aspects; Sustainable development; Circular economy (Closed loop economy).